Preparation method of low-interface reaction metal-based composite material based on powder solid-phase deposition
By employing powder solid-phase deposition additive manufacturing process and forced cooling technology, the problems of dispersion and interfacial reaction of reinforcing phases in metal matrix composites have been solved, achieving high density and excellent mechanical properties, especially for composites with reinforcing phases such as tungsten alloys and diamond.
Patent Information
- Application Number
- CN202511371147.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2025-12-30
AI Technical Summary
Metal matrix composites suffer from interfacial reactions and dispersion issues during preparation, resulting in performance values lower than theoretical values. This is especially true for reinforcing phases prone to interfacial reactions, such as tungsten alloy particles and diamond, which are difficult to effectively address with existing technologies.
The powder solid-phase deposition additive manufacturing process is adopted, which combines the frictional heat of the rotating tool and the substrate as a heat source to carry out deposition at a temperature lower than the melting point of the metal substrate. Through forced cooling and parameter control, the uniform dispersion of the reinforcing phase and the metal substrate and the controllable thickness of the interface reaction layer are achieved.
The uniform dispersion of the reinforcing phase in the matrix was achieved, the thickness of the interfacial reaction layer was reduced to the nanoscale, the material density was high, the plasticity and strength were significantly improved, and the interfacial reaction was reduced.
Smart Images

Figure CN121223104A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metal matrix composite material preparation and processing technology, specifically relating to a method for preparing low-interfacial-reaction metal matrix composites based on powder solid-phase deposition additive manufacturing. Through synergistic control of powder mixing and solid-phase deposition processes, uniform dispersion of the reinforcing phase and the metal matrix is achieved, along with suppression of interfacial reactions. This method is suitable for preparing composites with high volume fraction reinforcing phases (diamond, silicon carbide, etc.), especially reinforcing phase systems prone to interfacial reactions (tungsten particles, diamond, etc.). Background Technology
[0002] Metal matrix composites are multiphase materials formed by introducing one or more reinforcements into a metal or alloy matrix. The core purpose is to combine the toughness of the metal with the high strength, high modulus (such as SiC, TiC, TiB2), high thermal conductivity (such as diamond), and radiation absorption capacity (such as tungsten) of the reinforcement, thereby obtaining a material system with comprehensive performance superior to a single matrix.
[0003] However, interface and dispersion issues between the metal matrix and the reinforcing phase often lead to actual performance values of metal matrix composites that are significantly lower than their theoretical values. Dispersion problems are mainly due to the large density difference and poor wettability between the matrix and the reinforcing phase, which can easily cause agglomeration of the reinforcing phase during preparation, especially for metal matrix composites obtained through melting and casting processes or melt additive manufacturing. Interface problems typically include two aspects: one is the interfacial bonding strength, which makes it difficult for the reinforcing phase to effectively transfer loads; the other is the interfacial reaction. When composites are subjected to prolonged high temperatures, brittle phases are prone to appear at the interface, and cracks are more likely to initiate earlier at the interface, leading to a decrease in material plasticity. Furthermore, when diamond is used as the reinforcing phase, diamond and aluminum easily react to form Al4C3, reducing the thermal conductivity of the aluminum / diamond interface; when tungsten is used as the reinforcing phase, the aluminum matrix and tungsten particles easily form Al4W and Al2O3 at the interface. 12 W and other interface layers significantly reduce its radiation absorption capacity.
[0004] Currently, the preparation methods for metal matrix composites can be divided into solid-state methods and liquid-state methods based on whether the metal matrix melts during the preparation process. Liquid-state methods include stirred casting, spray deposition, and powder bed melting additive manufacturing. However, this is difficult for composites with reinforcing phases that are prone to interfacial reactions, such as tungsten alloy particles and diamond. Solid-state methods are mainly derived from powder metallurgy processes, while traditional hot pressing sintering-deformation processes are relatively cumbersome, and their maximum forming size is limited by equipment. Among solid-state methods, solid-state deposition additive manufacturing technology, which has been developed in recent years from stirred friction, has attracted widespread attention due to its advantages such as fast forming speed, fewer defects, and low residual stress. For example, CN117840569A discloses a solid-state additive manufacturing method for silicon carbide particle-reinforced aluminum matrix composite components, which uses extruded composite rods as deposition raw materials. This leads to a longer preparation process and increases the possibility of interfacial reactions. CN111804910A discloses a method and apparatus for friction stir forging additive manufacturing of nano-reinforced matrix composites, which involves friction stir additive processing of composite materials. It considers the reinforcing phase as multi-walled carbon nanotubes, graphene nanosheets, or titanium powder. It focuses on the equipment itself but lacks consideration for the actual process. The preparation process is prone to problems such as insufficient dispersion of the reinforcing phase and interfacial reactions. Summary of the Invention
[0005] The purpose of this invention is to provide a method for preparing low-interface-reaction metal matrix composites based on powder solid-phase deposition additive manufacturing, which can effectively solve the problems of long preparation process, poor interfacial bonding, and difficult processing and deformation of traditional metal matrix composites. In particular, it can enhance the strengthening effect of reinforcing phases such as tungsten alloy particles and diamond powder that are prone to interfacial reactions.
[0006] The complete technical solution of this invention includes:
[0007] A method for preparing low-interfacial-reaction metal matrix composites based on powder solid-phase deposition includes the following steps:
[0008] S1: Mixing nano or micron-sized reinforcing phase particles with metal matrix powder to form a composite powder;
[0009] S2: Powder solid-phase deposition additive manufacturing is performed at temperatures below the melting point of the metal substrate, using frictional heat between the rotating tool and the substrate / deposited layer as the only external heat source.
[0010] Furthermore, in step S2, during the powder solid-phase deposition additive manufacturing process, contact forced cooling is implemented on the deposition area, and the cooling rate is calculated based on the temperature data measured in real time by thermocouples during the experiment, so that the cooling rate is not less than a certain critical value, preferably 50℃ / s. This step is mainly to prevent the problem of increased interfacial reaction between the reinforcing phase and the aluminum matrix caused by the continuous thermal cycling of the deposited material during the deposition of multilayer bulk materials.
[0011] Furthermore, the forced cooling is achieved by spraying coolant or immersion cooling, with water or liquid nitrogen as the cooling medium.
[0012] Furthermore, in step S2, under the premise of forced cooling, the thickness of the composite material interface reaction layer is controllable by controlling the parameters of the powder solid phase deposition process.
[0013] Furthermore, the powder solid phase deposition process parameters include: tool rotation speed, axial pressure, shoulder radius, and tool travel speed.
[0014] The control method is as follows:
[0015]
[0016] In the formula, δ represents the thickness of the interfacial reaction layer, D0 is the diffusion constant, and Q is the diffusion activation energy. The diffusion constant and diffusion activation energy can be obtained from literature records or experimental data, or experimentally calculated by obtaining the thickness of the interfacial reaction layer at a certain temperature and holding time. The preferred D0 = 3.38 × 10⁻⁶. 18 m 2 / s, Q=580,000J / mol, R is the ideal gas constant, k is the temperature coefficient, which can be obtained through actual measurement and calculation, ω is the tool rotation speed, μ t Let be the friction coefficient between the tool shoulder and the material, F be the axial pressure during the deposition process, r be the radius of the tool shoulder, D = 2r be the diameter of the tool shoulder, and v be the tool moving speed.
[0017] Furthermore, the range of some parameters is as follows: tool shoulder diameter D is 16-100mm, tool speed ω is 150-3000rpm, tool movement speed v is 50-500mm / min, and axial pressure F is 0.5-30 tons.
[0018] Furthermore, the thickness of the additive layer is 0.5–2.0 mm.
[0019] Furthermore, by controlling the above parameters, the thickness of the composite material interface reaction layer is ≤30nm, and the material density is ≥99%.
[0020] Furthermore, in step S1, the powder mixing method includes mechanical mixing, high-energy ball milling mixing, or liquid phase mixing.
[0021] Furthermore, the metal matrix powder is selected from at least one of pure aluminum / aluminum alloy, pure copper / copper alloy, pure magnesium / magnesium alloy, pure iron / iron alloy, or pure titanium / titanium alloy.
[0022] Furthermore, the reinforcing phase particles are selected from at least one of tungsten powder, diamond, silicon carbide (SiC), titanium carbide (TiC), or titanium diboride (TiB).
[0023] Furthermore, the volume fraction of the reinforcing phase particles in the composite material is selected to be 5% to 60%. For composite powders with high volume fraction of reinforcing phase, it was found in experiments that the axial pressure during the deposition process can be increased to enhance the triaxial stress state of the material and thus improve its processing continuity. For example, when the volume fraction of the reinforcing phase is >20%, the axial pressure is 5 to 30 tons. While increasing the axial pressure, the tool moving speed can be increased to reduce the temperature of the deposition process. The increase in axial pressure can be achieved by reducing the layer thickness or increasing the powder conveying speed.
[0024] Furthermore, the metal matrix composite material prepared by the method described in the claims has an interfacial reaction layer thickness between the reinforcing phase and the metal matrix of ≤30 nm, a room temperature tensile elongation of ≥3% at any location, and a material density of ≥99%.
[0025] The interfacial reaction layer of the present invention was measured by TEM, and the density was measured by Archimedes' method.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The uniformity of the final reinforcing phase dispersion in the matrix is increased by pre-mixing the metal powder with the reinforcing phase.
[0028] 2. Existing technologies typically employ liquid-phase methods to prepare tungsten alloys and diamond composites. This invention utilizes a short-process powder solid-phase deposition additive manufacturing process. Through the synergistic effect of various parameters, the thickness of the interfacial reaction layer is controllable, reducing the interfacial reaction between the reinforcing phase and the matrix. While ensuring the material's density and plasticity, the interfacial reaction between the reinforcing phase and the matrix is reduced from the micron-level interfacial layer of conventional technologies to the nano-level interfacial layer. Attached Figure Description
[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the accompanying drawings used in the embodiments will be briefly described below. Referring to the accompanying drawings will provide a clearer understanding of the features and advantages of the present invention. The drawings are illustrative and should not be construed as limiting the present invention in any way. For those skilled in the art, other drawings can be obtained based on these drawings without any creative effort. Wherein:
[0030] Figure 1 This is a schematic diagram of the preparation process of the present invention.
[0031] Figure 2 The image shows the macroscopic morphology of the AZ31 / W alloy block prepared according to the present invention.
[0032] Figure 3 The microstructure of the AZ31 / W alloy bulk prepared according to the present invention.
[0033] Figure 4 The image shows the macroscopic morphology of the 6061 / W alloy block prepared according to the present invention.
[0034] Figure 5 The microstructure of the 6061 / W alloy bulk prepared according to the present invention.
[0035] Figure 6 The high-resolution TEM interface of the 6061 / W alloy bulk material prepared in this invention.
[0036] Figure 7 The high-resolution TEM interface of the 6061 / W alloy bulk material prepared in this invention. Detailed Implementation
[0037] To better understand the above-mentioned objectives, features, and advantages of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that, unless otherwise specified, the embodiments of the present invention and the features thereof can be combined with each other.
[0038] This invention discloses a method for preparing low-interfacial-reaction metal-based composite materials based on powder solid-phase deposition, the basic preparation process of which is as follows: Figure 1 As shown, the powder solid phase deposition additive manufacturing equipment used can be referred to the applicant's earlier application CN117161406A, an additive manufacturing apparatus and manufacturing method based on powder feeding type stirred friction deposition.
[0039] Example 1
[0040] S1. Tungsten metal particles and AZ31 magnesium alloy powder are mechanically mixed at a volume ratio of 3:7, and the average particle size of the tungsten particles is ~30 micrometers.
[0041] S2. Perform powder solid-phase deposition additive manufacturing on the composite powder, with specific parameters including: tool shoulder diameter of 38mm, tool rotation speed of 350rpm, tool moving speed of 200mm / min, axial pressure of 6 tons, and additive layer thickness of 0.6mm.
[0042] S3. During the deposition process in step S2, the deposition area is subjected to forced cooling at a rate of ≥50℃ / s.
[0043] Comparative Example 1:
[0044] S1. Tungsten metal particles and AZ31 magnesium alloy powder are mechanically mixed at a volume ratio of 3:7, and the average particle size of the tungsten particles is ~30 micrometers.
[0045] S2. Perform powder solid-phase deposition additive manufacturing on the composite powder, with specific parameters including: tool shoulder diameter of 38mm, tool rotation speed of 350rpm, tool movement speed of 60mm / min, axial pressure of 3 tons, and additive layer thickness of 1.0mm;
[0046] S3. During the deposition process in step S2, the deposition area is subjected to forced cooling at a rate of ≥50℃ / s.
[0047] Due to the high volume fraction of the reinforcing phase, the prepared surface exhibits discontinuities, with less than 1% plasticity at the defects.
[0048] The difference between Example 1 and Comparative Example 1 is that the thickness of the additive layer was reduced while the axial pressure of the deposition process was increased. Although the tool moving speed was increased to 200 mm / min, the deposited bulk alloy was successfully prepared. Figure 2 Macroscopic morphology images of the prepared AZ31 / W alloy bulk are shown. Figure 3 The microstructure of the prepared bulk material is presented, showing a magnesium alloy matrix with uniformly distributed W particles and an interface layer thickness of 22 nm. The material's density, measured by Archimedes' displacement method, is 99.8%. The yield strength is 233 MPa, the tensile strength is 300 MPa, and the elongation is 11%.
[0049] Example 2
[0050] S1. Tungsten metal particles and 6061 aluminum alloy powder are mechanically mixed at a volume ratio of 1:9, and the average particle size of the tungsten particles is ~30 micrometers.
[0051] S2. Perform powder solid-phase deposition additive manufacturing on the composite powder, with specific parameters including: tool shoulder diameter of 38mm, tool rotation speed of 350rpm, tool moving speed of 200mm / min, axial pressure of 3 tons, and additive layer thickness of 1.0mm;
[0052] S3. During the deposition process in step S2, the deposition area is subjected to forced cooling at a rate of ≥50℃ / s.
[0053] Figure 4 The macroscopic microstructure of the bulk material prepared using the above parameters is presented. The initial bulk material dimensions are 100 mm (length) × 40 mm (width) × 20 mm (height). Figure 5 The microstructure morphology of the prepared bulk material is shown, with W particles uniformly distributed in an aluminum matrix. Figure 6The high-resolution interface between the aluminum matrix and W particles is presented, revealing that the interface layer thickness is below 15 nm. This thickness helps enhance the strengthening effect of the W particles while maintaining a certain interfacial strength. For composite materials prepared using conventional liquid-phase methods, the interface layer thickness can even exceed 1 μm. The material's density, measured by Archimedes' displacement method, is 99.8%. After T6 heat treatment, the yield strength is 257 MPa, the tensile strength is 337 MPa, and the elongation is 8%.
[0054] Comparative Example 2
[0055] S1. Tungsten metal particles and 6061 aluminum alloy powder are mechanically mixed at a volume ratio of 1:9, and the average particle size of the tungsten particles is ~30 micrometers.
[0056] S2. Perform powder solid-phase deposition additive manufacturing on the composite powder, with specific parameters including: tool shoulder diameter of 38mm, tool rotation speed of 350rpm, tool movement speed of 200mm / min, axial pressure of 3 tons, and additive layer thickness of 1.0mm.
[0057] The difference between this embodiment and Embodiment 1 is that forced cooling was not enabled. Figure 7 The high-resolution interface between the aluminum matrix and W particles is presented, showing that the thickness of the interface layer at the bottom of the deposited bulk material increased to ~40 nm due to repeated thermal cycling. The material's density, measured by Archimedes' displacement method, was 99.9%. After T6 heat treatment, the material's yield strength was 220 MPa, tensile strength was 290 MPa, and elongation was 6%. The mechanical properties of the material were significantly reduced compared to the forced-cooled bulk material.
[0058] Example 3
[0059] S1. Diamond particles and pure aluminum powder are mechanically mixed at a volume ratio of 2:8, and the average particle size of the diamond particles is ~80 micrometers.
[0060] S2. Perform powder solid-phase deposition additive manufacturing on the composite powder, with specific parameters including: tool shoulder diameter of 38mm, tool rotation speed of 350rpm, tool moving speed of 150mm / min, axial pressure of 6 tons, and additive layer thickness of 0.7mm.
[0061] S3. During the deposition process in step S2, the deposition area is subjected to forced cooling at a rate of ≥50℃ / s.
[0062] The material's density was 99.3% as determined by the Archimedes displacement method, and no Al4C3 brittle phase was observed during microstructure analysis.
[0063] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for the production of low interfacial reaction metal matrix composites based on powder solid phase deposition, characterized in that, The method comprises the following steps: S1: mixing nano or micro-sized reinforcing phase particles with metal matrix powder to form a composite powder; S2: performing powder solid-phase deposition additive manufacturing at a temperature lower than the melting point of the metal matrix by using friction heat between a rotating tool and the substrate / deposited layer as the only external heat source.
2. The method for manufacturing a low interfacial reaction metal matrix composite based on powder solid deposition according to claim 1, characterized in that, During the powder solid-phase deposition additive manufacturing process in step S2, the deposition area is subjected to contact forced cooling.
3. The method of claim 2, wherein the powder-based solid deposition of a low- interfacial reaction metal matrix composite is characterized by: The forced cooling is achieved by spraying a cooling liquid or by immersion cooling, and the cooling medium is water or liquid nitrogen.
4. The method of claim 3, wherein the powder-based solid deposition of a low- interfacial reaction metal matrix composite is characterized by: In step S2, the thickness of the interface reaction layer of the composite material is controlled by controlling the powder solid-phase deposition process parameters.
5. The method of claim 4, wherein the powder-based solid deposition of a low- interfacial reaction metal matrix composite is characterized by: The powder solid-phase deposition process parameters include tool rotation speed, axial pressure, shaft shoulder radius, and tool movement speed.
6. The method of claim 1, wherein the powder-based solid deposition of a low- interfacial reaction metal matrix composite is characterized by: In step S1, the powder mixing method includes mechanical mixing, high-energy ball milling mixing, or liquid-phase mixing.
7. The method of claim 1, wherein the powder-based solid deposition of a low- interfacial reaction metal matrix composite is characterized by: The metal matrix powder is selected from at least one of pure aluminum / aluminum alloy, pure copper / copper alloy, pure magnesium / magnesium alloy, pure iron / iron alloy, or pure titanium / titanium alloy.
8. The method of claim 1, wherein the powder-based solid deposition of a low- interfacial reaction metal matrix composite is characterized by: The reinforcing phase particles are selected from at least one of tungsten powder, diamond, silicon carbide (SiC), titanium carbide (TiC), or titanium diboride (TiB).
9. The method of claim 8, wherein the powder-based solid deposition of a low- interfacial reaction metal matrix composite is characterized by: The volume fraction of the reinforcing phase particles in the composite material is 5% to 60%.
10. Metal matrix composite produced by the method according to any one of claims 1 to 9; characterized in that The interface reaction layer thickness of the reinforcing phase and the metal matrix is ≤30 nm, the room temperature tensile elongation at any position is ≥3%, and the material density is ≥99%.
Citation Information
Patent Citations
Stirring friction forging additional material manufacturing method and device of nano reinforcing composite materials
CN111804910A
Additive manufacturing device and manufacturing method based on powder feeding type friction stir deposition
CN117161406A
Solid-state additive manufacturing method of silicon carbide particle reinforced aluminum matrix composite component
CN117840569A
